Optimal cycling time trial position models: aerodynamics versus power output and metabolic energy - Fintelman, D. M.; Sterling, M.; Hemida, H.; Li, F.-X. (Journal of Biomechanics, 2014)
The aerodynamic drag of a cyclist in time trial (TT) position is strongly influenced by the torso angle. While decreasing the torso angle reduces the drag, it limits the physiological functioning of the cyclist. Therefore the aims of this study were to predict the optimal TT cycling position as function of the cycling speed and to determine at which speed the aerodynamic power losses start to dominate. Two models were developed to determine the optimal torso angle: a `Metabolic Energy Model' and a `Power Output Model'. The Metabolic Energy Model minimized the required cycling energy expenditure, while the Power Output Model maximized the cyclists' power output. The input parameters were experimentally collected from 19 TT cyclists at different torso angle positions (0-24°). The results showed that for both models, the optimal torso angle depends strongly on the cycling speed, with decreasing torso angles at increasing speeds. The aerodynamic losses outweigh the power losses at cycling speeds above 46 km/h. However, a fully horizontal torso is not optimal. For speeds below 30 km/h, it is beneficial to ride in a more upright TT position. The two model outputs were not completely similar, due to the different model approaches. The Metabolic Energy Model could be applied for endurance events, while the Power Output Model is more suitable in sprinting or in variable conditions (wind, undulating course, etc.). It is suggested that despite some limitations, the models give valuable information about improving the cycling performance by optimizing the TT cycling position.